2017
DOI: 10.1155/2017/3918681
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Microvesicle-Bound Uromodulin: A Potential Molecular Biomarker in Diabetic Kidney Disease

Abstract: This study was designed to investigate the changes of urinary microvesicle-bound uromodulin and total urinary uromodulin levels in human urine and the correlations with the severity of diabetic kidney disease (DKD). 31 healthy subjects without diabetes and 100 patients with type 2 diabetes mellitus (T2DM) were included in this study. The patients with T2DM were divided into three groups based on the urinary albumin/creatinine ratio (UACR): normoalbuminuria group (DM, n = 46); microalbuminuria group (DN1, n = 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…This was most likely due to limitations in the exosome extraction method from plasma and the high lipid content in the exosomal preparation that interfered with the HPLC separation. In addition, large vesicles were isolated from plasma and urine by immunoprecipitation using an antibody against AD-1, an extracellular vesicle marker (25)(26)(27)(28). Immunoprecipitated extracts analyzed by Western blotting confirmed that HSP27 was present in extracellular vesicles (Supplemental Fig.…”
Section: Ms Detection Of Hsp27 Isolated From Human Plasma Extracellulmentioning
confidence: 91%
See 1 more Smart Citation
“…This was most likely due to limitations in the exosome extraction method from plasma and the high lipid content in the exosomal preparation that interfered with the HPLC separation. In addition, large vesicles were isolated from plasma and urine by immunoprecipitation using an antibody against AD-1, an extracellular vesicle marker (25)(26)(27)(28). Immunoprecipitated extracts analyzed by Western blotting confirmed that HSP27 was present in extracellular vesicles (Supplemental Fig.…”
Section: Ms Detection Of Hsp27 Isolated From Human Plasma Extracellulmentioning
confidence: 91%
“…An antibody against AD1, a protein found on hepatic plasma membranes, has been shown (25)(26)(27)(28) to be useful as a microvesicle marker. Hence, we employed the AD1 antibody to isolate microvesicles from plasma and urine taken from healthy human participants using immunoprecipitation.…”
Section: Immunoprecipitation Of Extracellular Vesicles From Human Plamentioning
confidence: 99%
“…In particular, we applied several controls for each downstream analysis; this is especially important for flow cytometry analysis as many particles can mimic EVs. One of the major drawbacks of enriching uEVs is the co-sedimentation of THP, which can sediment readily at very low speed 25 and entrap uEVs in its filaments 18 or bind EVs 26 . Thus, one of our main goals was to reduce THP interference for MS analysis, RNA extraction and miRNA quantification, and NTA enumeration.…”
Section: Discussionmentioning
confidence: 99%
“…Urine samples were collected at the earliest visit during the above observation period and stored at À80 to À85 ℃ until measurement. Next, 30 urinary biomarkers that could be measured at the internal or external laboratory were selected from urinary biomarkers reported by previous studies [1][2][3][4][5][8][9][10][11] to be involved in diabetic nephropathy (Table 1). These included novel biomarkers which were classified according to their modes of action as follows: inflammation, fibrosis, angiogenesis, mineral metabolism, glomerular injury, tubular injury and thick ascending limb injury.…”
Section: Biomarker Assaysmentioning
confidence: 99%